114k views
3 votes
Solve for P
6p - 2 - 3p = 4

Solve for W
7w - 5 = -2w + 22

User MatAff
by
4.9k points

2 Answers

4 votes

Answer:

p = 2

w = 3

Explanation:

Solve for P

6p - 2 - 3p = 4

6p - 3p = 4 + 2

3p = 6

p = 6/3

p = 2

Solve for W

7w - 5 = -2w + 22

7w + 2w = 22 + 5

9w = 27

w = 27/9

w = 3

User Krodmannix
by
6.6k points
4 votes

Answer:

p=2 w=3

Explanation:

6p-2-3p=4 combine like terms. 3p-2=4. add 2 to both sides. 3p=6. divide 6 both sides by 3. p=2

7w-5=-2w+22. Combine like terms on same sides. 7w+2w=5+22. 9w=27. Divide both sides by 9. w=3.

User Ziq
by
5.7k points